PENGARUH METODE LATIHAN SIRKUIT TERHADAP KEMAMPUAN LOMPAT JAUH GAYA JONGKOK SMK TEKNOLOGI RIAU - Ahmad Yani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
%DVHG RQWKH UHVHDUFKHU¶V REVHUYDWLRQ RQWKHILHOGLW VHHPVWKDWWKH DELOLW\ RI VWXGHQWV RI 60.7HNQRORJL5LDXLQORQJMXPSLV VWLOOORZDQGPDQ\ VWXGHQWV GRQ¶WKDYHJRRGHQRXJK techniques of long jump itself, besides that, the training method that is used is not appropriate yet. The purpose of this research is to find out the effect of circuit training method towards WKH VWXGHQWV¶ ORQJ MXPS DELOLW\ DW 60. 7HNQRORJL 5LDX This type of this research is Experimental using T-test, the population of this research in class XI of SMK Teknologi Riau consist of 11 male students. The result of data analysis shows that : (1) There are different of result of long jump ability in circuit method (Thitung = 4.75 > Ttabel = 1.812),. So that is why Thitung bigger than Ttable its mean there is significant effect in using circuit method towardsLong Jump of SMK Teknologi Riau students.